Determinants of Stillbirth Among Deliveries Attended in Bale Zone Hospitals, Oromia Regional State, Southeast Ethiopia: A Case–Control Study - Mekonnen Dagne H; Takele Melku A; Abdurkadir Abdi A (Dove Medical Press, 2021)
Henok Mekonnen Dagne,1 Abulie Takele Melku,1 Adem Abdurkadir Abdi2 1World Vision Ethiopia, Hawassa, Ethiopia; 2Department of Public Health, Madda Walabu University Goba Referral Hospital School of Health Science, Bale Goba, EthiopiaCorrespondence: Abulie Takele MelkuDepartment of Public Health, Madda Walabu University Goba Referral Hospital School of Health Science, PO Box 302, Bale Goba, EthiopiaTel +251911060837Email Abuletakele@Yahoo.ComBackground: Stillbirth is one of the adverse outcomes of pregnancy, and it is among the major public health problems in developing countries including Ethiopia. Stillbirth has wide-reaching consequences for parents, care providers, community and society at large.Purpose: To assess the determinant of stillbirth among deliveries attended in Bale zone hospitals Southeast Ethiopia.Methods: An institution-based unmatched case–control study was conducted. Cases were deliveries whose birth outcome was stillbirth and controls were deliveries with live birth. A pretested and structured checklist was used to collect data from a sample of 402 (134 cases and 268 controls). Systematic random sampling was used to recruit samples from a list of charts in the delivery registration book. Data were entered into EpiData version 4.2 and exported to SPSS version 20 for analysis. Crude and adjusted odds ratio with 95%CI was calculated and P-value < 0.05 was used to declare statistical significance.Results: A total of 402 charts of mothers (134 cases and 268 controls) were included in the analysis. Preceding birth interval < 24 months (AOR: 2.991; 95%CI: 1.351– 6.621), antenatal visit started at third trimester (AOR: 2.739; 95%CI: 1.048– 7.158), referred from other health facility (AOR: 3.215; 95%CI: 1.430– 7.229), labor length ≥ 24 h (AOR: 3.169; 95%CI: 1.241– 8.091), presence of meconium stained amniotic fluid (AOR: 2.670; 95%CI: 1.082– 6.592) and giving birth to a baby < 2500 g (AOR: 3.155; 95%CI: 1.235– 8.07) were determinants of stillbirth.Conclusion: Preceding birth interval of < 24 months, antenatal visit started at third trimester, referred from other health facility, presence of meconium stained amniotic fluid, labor length ≤ 24 h and giving birth to a baby < 2500 g were found the determinants of stillbirth. Intrapartum care, early identification of labor complications and referral system are required.Keywords: stillbirth, determinant, cases, controls